Pucuk Rebung Catering Online Booking System (PRCOBS) / Ashiqin Nur Sarudin - Sarudin, Ashiqin Nur (2017)
Pucuk Rebung Catering Online Booking System (PRCOBS) is online management information where a case study has been done at Pucuk Rebung Catering (PRC). Currently, they use the manual process to manage their business activities with the customer. The customers need to make the booking as manually by coming to the PRC office or by using the telephone. The model used for PRCOBS is adapted Waterfall Model which has several phases such as Requirement Analysis, Design, Implementation and Testing. Besides that, system testing plan and evaluation from users and experts also has been prepared to improve the functionality, usability and interface design of the system. The system has been tested by three (3) expert users and thirty (30) respondents. The highest mean is 4.13 with the standard deviation of 0.507 has been achieved for the perceived usefulness evaluation. Overall, the system is satisfied to be used by the user in order to complete their booking.